2016
DOI: 10.3390/s16122029
|View full text |Cite
|
Sign up to set email alerts
|

Uniformly Porous Nanocrystalline CaMgFe1.33Ti3O12 Ceramic Derived Electro-Ceramic Nanocomposite for Impedance Type Humidity Sensor

Abstract: Since humidity sensors have been widely used in many sectors, a suitable humidity sensing material with improved sensitivity, faster response and recovery times, better stability and low hysteresis is necessary to be developed. Here, we fabricate a uniformly porous humidity sensor using Ca, Ti substituted Mg ferrites with chemical formula of CaMgFe1.33Ti3O12 as humidity sensing materials by solid-sate step-sintering technique. This synthesis technique is useful to control the grain size with increased porosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Compared with other films for humidity sensing, the as‐fabricated GOA film possessed competitive ultrafast response time in a thicker case, which had more space to improve responsiveness. It can be observed that the response time decreased with decreased thickness for the same type materials, such as the GO‐based films (pink dotted line) and rGO‐based films (blue dotted line) in the figure . In the ultrafast response region marked as yellow, there were three films with the response time smaller than 100 ms. GOA film can maintain ultrafast response at 140 μm thickness, whereas other two films holding ultrafast response were limited to a thickness less than 1 μm.…”
Section: Resultsmentioning
confidence: 91%
“…Compared with other films for humidity sensing, the as‐fabricated GOA film possessed competitive ultrafast response time in a thicker case, which had more space to improve responsiveness. It can be observed that the response time decreased with decreased thickness for the same type materials, such as the GO‐based films (pink dotted line) and rGO‐based films (blue dotted line) in the figure . In the ultrafast response region marked as yellow, there were three films with the response time smaller than 100 ms. GOA film can maintain ultrafast response at 140 μm thickness, whereas other two films holding ultrafast response were limited to a thickness less than 1 μm.…”
Section: Resultsmentioning
confidence: 91%
“…Due to single hydrogen bonding, water molecules move freely and were ionized due to the application of external electric field. As a result, more number of hydronium ions (H 3 O + ) were formed and deposited at the grain and grain‐boundary interface, and thus enhanced the dielectric properties of the composite at higher humid condition …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we aimed to design and develop a porous armalcolite nanocomposite‐based humidity sensor in order to analyze their dielectric response at different RH conditions. According to our previous reports, the capacitive and resistive properties of the armalcolite‐based nanocomposite as a function of RH have only been explored until now . In the present work, the RH‐dependent dielectric constant (ɛʹ), ɛʺ, tanδ, alternating current conductivity (σ ac ) along with hysteresis, response time, recovery time, stability and humidity‐sensing mechanism of armalcolite nanocomposite‐based sensor had been studied.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the wide application range of devices being able to record humidity is behind the intensive scientific studies dedicated to this area. Their most important fields of use are indoor application, plants growth in agricultural market, and control of industrial processes, electronics, and semiconductor area, as well as medical processes [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%